Amino Acid-Based Formula vs. Extensively Hydrolyzed Formula in the Treatment of Feeding Intolerance in Preterm Infants: Study Protocol for a Randomized Controlled Trial - Zhong, Qin; Lu, Qi; Peng, Nan; Liang, Xiao-Hua (Frontiers in Nutrition, 2022)
Background: Feeding intolerance is a common problem in preterm infants, which is associated with increased risk of infections, prolonged hospitalization, and increased economic costs. When human milk is not available, formula feeding is required. Amino acid-based formula and extensively hydrolyzed formula could be considered to use for severe feeding intolerance. A recent Cochrane meta-analysis found that preterm infants fed extensively hydrolyzed formula compared with standard formula could not reduce the risk of feeding intolerance and necrotizing enterocolitis, and weight gain was slower. Some studies reported that preterm infants fed amino acid-based formula could reduce the gastric residual volume. We hypothesize that amino acid-based formula can improve feeding intolerance and establish full enteral feeding more rapidly in preterm infants compared with extensively hydrolyzed formula. Method: The randomized, prospective, controlled trial is to be conducted in Children's Hospital of Chongqing Medical University (Chongqing, China). A total of 190 preterm infants with gestational age < 32 weeks or birth weight < 1500g and with a diagnosis of feeding intolerance will be included. Patients will be randomized to an amino acid-based formula-fed group and an extensively hydrolyzed formula-fed group. The primary outcome is the time (days) to reach full enteral feedings. Secondary outcomes include duration of vomiting and abdominal distension, gastric residual volume, body weight, length and head circumference during hospitalization, length of hospital stay (days), cost of hospitalization, time (days) of parenteral nutrition, change of abdomen circumference, main serum parameters and incidence of adverse events. Discussion: The successful implementation of our study will provide robust evidence for formula alternatives in preterm infants with feeding intolerance. Trial registration: This study has been registered within ClinicalTrials.gov (NCT05347706) and the Chinese Clinical Trial Registry (ChiCTR2100048475). Keywords: feeding intolerance, preterm infant, amino acid-based formula，extensively hydrolyzed formula, randomized controlled trial, protocol